Transforming Agrifood Systems in West and Central Africa Initiative (TAFS-WCA): Baseline report of the TAFS-WCA - Arouna, A.; Yergo, Wilfried; Aboudou, R.; Ouédraogo, M.; Abdoulaye, Tahirou (Africa Rice Center, 2023)
This report presents the baseline survey of the Transforming Agrifood Systems in West and Central Africa initiative (TAFS-WCA) in Cote d'Ivoire and Ghana. Five areas in Cote d'Ivoire and four areas in Ghana were surveyed. Data was collected using a smart tablet with the CSPro application. A total of 1207 and 1200 actors were surveyed during the baseline data collection in Cote d’Ivoire and Ghana, respectively. Actors involved in the baseline data collection are producers of rice, maize, beans, yams, cassava, banana, cocoa, African vegetables, inputs dealer, traders, processors and service providers. All analyses in this paper were carried out using the STATA 16 statistical software. Among the population of producers, 27.05% (651) are rice producers, 11.97% (288) are maize producers, 4.86% (117) are beans producers, 9.89% (238) are yams producers, 10.93% (263) are cassava producers, 2.49% (60) are sweet potatoes producers, 4.11% (99) are banana producers, 9.18% (221) are cocoa producers, 4.15% (100) are African vegetables producers, 1.04% (25) inputs dealer, 7.23% (174) are traders, 2.16% (52) are processors and 4.61% (111) are service providers. The average age of rice farmers is 46 years old and ranges from 18 to 85 years old, and the average household size is 8 people. About 65.50% of actors are male and 84.34% are married. In addition, 52% of the actors have received formal education and 83.42% have crop production has main activity. Moreover, 53 % of producers produce during the rainy season, 13% during the dry season and 34% during both seasons. It should also be noted that in the face of climate change, 26% of producers have access to information on weather forecasts (for today, 24 hours and/or next 2-3 days), 20% to forecasts of extreme events (drought, flood, strong wind, etc.), and 19% to information on seasonal forecasts (weather for the following 2-3 months). In relation to food security and the poverty index, preliminary results showed that the vast majority of farmers households in both countries have an acceptable level of dietary diversity, meal frequency and nutritional importance of the food groups consumed; and the poverty index of the population remains was 48%.